Sejarah Pakaian Adat Masyarakat Kajang Kabupaten Bulukumba (Studi Etnografi Komunikasi) - Ikram, Ikramullah Mahdi; Mau, Muliadi; Arianto, Arianto (Program Pascasarjana, UIN Alauddin Makassar, 2023)
This research was conducted in Tanah Toa Village, Kajang District, Bulukumba Regency, South Sulawesi, which until now still adheres to the beliefs of its ancestors, one of which is wearing all-black clothes which are considered sacred and sacred. This research method is descriptive qualitative and uses an ethnographic communication approach. Data was collected by means of observation, interviews, literature and documentation. The purpose of this study was to describe the history and traditions of the Ammatoa Kajang ethnic community's traditional clothing, Bulukumba Regency. The results of this research on the history and traditions of the Kajang tribe's traditional clothing are a marker of the cultural identity of the Ammatoa ethnic community, which illustrates the belief that humans are born from the realm of darkness until the end of their lives they also return to the realm of darkness. Carrying out the Ammatoa ancestral tradition as the highest customary leader who also used traditional clothing in the past, reflecting adherence to customary law (Pasang) especially the principle of attallasa' kamase-mase or living modestly/simplely, representing equality for everyone before God (Turiek Akra 'na), a sense of equality and a shared destiny. Abstrak Penelitian ini dilakukan di Desa Tanah Toa Kecamatan Kajang Kabupaten Bulukumba Sulawesi Selatan yang sampai saat ini masih memegang erat keperyaan para leluhurnya, salah satunya yaitu menggunakan pakain serba hitam yang dianggap sebagai pakaian yang suci dan sakral. Metode penelitian ini deskriptif kualitatif dan menggunakan pendekatan etnografi komunikasi. Data dikumpulkan dengan cara observasi, wawancara, kepustakaan dan dokumentasi. Tujuan penelitian ini untuk mendiskripsikan sejarah dan tradisi pakaian adat komunitas etnik Ammatoa Kajang Kabupaten Bulukumba. Hasil penelitian ini pada sejarah dan tradisi pada pakaian adat suku kajang merupakan penanda identitas kultural komunitas etnik Ammatoa, yang menggambarkan kepercayaan bahwa manusia terlahir dari alam kegelapan hingga akhir hayatnya juga kembali ke alam kegelapan. Melaksanakan tradisi leluhur Ammatoa sebagai pimpinan adat tertinggi yang juga menggunakan pakaian adat di masa lalu, mencerminkan ketaatan pada hukum adat (Pasang) khususnya prinsip attallasa’ kamase-mase atau hidup bersahaja/sederhana, merepresentasikan kesamaan derajat bagi setiap orang di depan tuhan (Turiek Akra’na), rasa persamaan dan senasib sepenanggungan.